2017
DOI: 10.2166/wst.2017.172
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of duckweed ponds used for nutrient recovery from wastewater

Abstract: The microorganism community that grows under duckweed shelter can play an important role on treatment processes. Therefore, the present study aimed to assess the zooplankton dynamic and microbial community in duckweed ponds (DPs) applied for domestic wastewater treatment under open field conditions. A pilot system comprised of two DPs in series (DP1 and DP2), with 10 m each, received domestic wastewater through a flow rate of 200 L·day. Thus, the system was monitored during 314 days through samples collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…6 Duckweed uptake, which was far beyond microbial contribution, was the main way to N removal in duckweed system. 20 In the rst 10 days, the TN concentration in the S. polyrhiza K1-based system decreased below 1.5 mg L À1 (corresponded to the standard of Grade IV which is mainly applicable to the water areas for industrial use according to CSWEQS), while TN concentrations of L. minor K2, L. punctata K3 and the polyculture duckweed were all over 1.5 mg L À1 (Table 2). Then TN concentration gradually declined to below 1.0 mg L À1 at the end of the experiment, with the highest TN removal efficiency of 98.8% for S. polyrhiza K1, 98.5% for L. minor K2 and 95.6% for L. punctata K3 and 99.1% for the polyculture, respectively (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…6 Duckweed uptake, which was far beyond microbial contribution, was the main way to N removal in duckweed system. 20 In the rst 10 days, the TN concentration in the S. polyrhiza K1-based system decreased below 1.5 mg L À1 (corresponded to the standard of Grade IV which is mainly applicable to the water areas for industrial use according to CSWEQS), while TN concentrations of L. minor K2, L. punctata K3 and the polyculture duckweed were all over 1.5 mg L À1 (Table 2). Then TN concentration gradually declined to below 1.0 mg L À1 at the end of the experiment, with the highest TN removal efficiency of 98.8% for S. polyrhiza K1, 98.5% for L. minor K2 and 95.6% for L. punctata K3 and 99.1% for the polyculture, respectively (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…As evidenced by previous studies, microbial nitrication and denitrication occurred in duckweed system. 20,45 For instance, Teles et al found that 40 genera of bacteria exhibited high abundance in duckweed system, including functional groups as nitrifying bacteria (Nitrospira and Nitrosomonas) and denitrifying bacteria (Rhodopseudomonas). 20 However, unlike activated sludge system, microbial nitrication/denitrication was the predominant route of N removal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, since a slight stimulus in the growth of plants exposed to the effluent from the elC treatment was observed, a sufficient removal of metal ions ceasing to be toxic and behaviour like nutrients can be inferred. As macrophytes need nutrients for their development (Teles et al 2017), the results suggest that the treated effluent may have a nutrient function for the duckweed.…”
Section: Toxicological Assay For Growth and Inhibition Ratementioning
confidence: 95%